2018
DOI: 10.1177/1063293x18805200
|View full text |Cite
|
Sign up to set email alerts
|

Product evolutionary design driven by environmental performance

Abstract: This article is in terms of product environmental performance demand and proposes four structure evolutionary operation modes which include combined evolutionary method, decomposition evolutionary method, replacement evolutionary method, and material-changing evolutionary method to express the structure evolutionary process of products. Through the quotient space theory and proposed method combined with probability statistics, probability mapping from environmental performance to product structure is establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…However, typical product evolution is reflected in product structure evolution. Zhang et al [25] proposed four structural evolution operation modes: combination evolution method, decomposition evolution method, substitution evolution method, and material change evolution method, and described product structure evolution from the requirements of product environmental performance. Li et al [26] analyzed the complexity, importance, and robustness of product structure, revealed the evolution characteristics of product structure based on a time-varying network model, and provided designers with product development direction.…”
Section: Product Evolutionmentioning
confidence: 99%
“…However, typical product evolution is reflected in product structure evolution. Zhang et al [25] proposed four structural evolution operation modes: combination evolution method, decomposition evolution method, substitution evolution method, and material change evolution method, and described product structure evolution from the requirements of product environmental performance. Li et al [26] analyzed the complexity, importance, and robustness of product structure, revealed the evolution characteristics of product structure based on a time-varying network model, and provided designers with product development direction.…”
Section: Product Evolutionmentioning
confidence: 99%